2012
DOI: 10.1071/fp12033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on the reproductive development of chickpea genotypes under controlled environments

Abstract: High temperature during the reproductive stage in chickpea (Cicer arietinum L.) is a major cause of yield loss. The objective of this research was to determine if that variation can be explained by differences in anther and pollen development under heat stress. Therefore the effect of high temperature during the pre-and postanthesis periods on pollen viability, pollen germination in a medium, pollen germination on the stigma, pollen tube growth and pod set in a heat tolerant (ICCV 2 92944) and a heat sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 167 publications
(149 citation statements)
references
References 33 publications
7
140
0
2
Order By: Relevance
“…In vitro pollen germination has been used to screen heat tolerance in many crops (Kakani et al 2002(Kakani et al , 2005Salem et al 2007;Devasirvatham et al 2012;Song et al 2015;Singh et al 2015Singh et al , 2016. On the other hand, Petkova et al (2009) suggested that to assess heat-tolerant cultivars of field pea, in vitro pollen-tube length is more reliable than pollen germination percentage because successful fertilization depends on whether pollen tubes actually reach the ovules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro pollen germination has been used to screen heat tolerance in many crops (Kakani et al 2002(Kakani et al , 2005Salem et al 2007;Devasirvatham et al 2012;Song et al 2015;Singh et al 2015Singh et al , 2016. On the other hand, Petkova et al (2009) suggested that to assess heat-tolerant cultivars of field pea, in vitro pollen-tube length is more reliable than pollen germination percentage because successful fertilization depends on whether pollen tubes actually reach the ovules.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, with 64-72% of genes in vegetative tissues of Tradescantia and maize also being expressed in pollen (reviewed by Hamilton and Mascarenhas, 1997), in vitro pollen germination has been investigated as a rapid screening criterion for tolerance to a variety of agronomically-important characteristics including soil acidity and salinity, metal and herbicide toxicity, as well as for heat tolerance (Sari-Gorla and Frova, 1997). Exposure to high temperatures reduces in vitro pollen germination percentage and pollen-tube length in many crops including canola (Singh et al 2008;Morrison et al 2016), cotton (Kakani et al 2005Song et al 2015), and sorghum (Nguyen et al 2013;Djanaguiraman et al 2014;Singh et al 2015Singh et al , 2016, as well as legumes like chickpea (Cicer arietinum; Devasirvatham et al 2012), field pea (Pisum sativum; Petkova et al 2009;Lahlali et al 2014;Jiang et al 2015), groundnut (Arachis hypogaea; Kakani et al 2002), and soybean (Glycine max; Koti et al 2005;Salem et al 2007). In sorghum, seed-set percentage (the number of seeds filled at physiological maturity divided by the total number of florets) was strongly and positively associated with in vitro pollen germination across genotypes and temperature regimes (Nguyen et al 2013;Singh et al 2015Singh et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…At the metabolic level, the heattolerant genotypes appeared to possess a stable and more active antioxidative defense mechanism than their sensitive counterparts. Devasirvatham et al [77] reported that the high temperatures reduced pod set in chickpea by reducing pollen viability and pollen production per flower. The pollen of the heat-tolerant line ICCV 92944 was viable at 35/20 C (41% fertile) and at 40/25 C (13% fertile), while the pollen of the heat-sensitive line ICC 5912 was completely sterile at 35/20 C with no in vitro germination and no germination on the stigma.…”
Section: Physiological Mechanisms Underlying Heat Tolerancementioning
confidence: 99%
“…Earlier work has shown that pollen viability and pod set in chickpea is affected at 35/20˚C under controlled environments (Devasirvatham et al, 2010). Under controlled conditions, pollen production is reduced at 35/20˚C thus demonstrating that pollen is more sensitive to high temperature in chickpea 4 (Devasirvatham et al, 2012). In vitro pollen germination and tube growth studies of chickpea showed that 35˚C and 45˚C reduced germination as compared to that observed at 25˚C (Jaiwal and Mehta, 1983).…”
Section: Introductionmentioning
confidence: 97%